(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The word surfactant is a blend of surface active agents. The surfactants are typically organiccompounds that are amphiphilic. Surfactant amphiphile are two terms that are occasionally usedinterchangeably. The phrase refers to the fact that all surfactant molecules have at least two components,tthat is soluble in a certain fluid (the lyophilic part) and the other of which is insoluble in that fluid (theinsoluble part) (the lyophobic part). When the fluid is water, the hydrophilic and hydrophobic parts arefrequently discussed. The interfacial adsorption micellization of SDS in aqueous liquid-vapor PEG ofvarious chain lengths were investigated using surface tension, conductance, spectrophotometricmethods.